The Genetic Domestication of Clostridium carboxidivorans - Morris, William (2025)
The continued use of fossil fuels to produce energy and chemicals is becoming increasingly untenable. They are a finite resource responsible for the release greenhouse gases into the atmosphere, directly contributing to global warming and climate change. If the consumption of fossil fuels remains unabated then drastic environmental consequences are inevitable. A promising alternative is exploiting the potential of microorganisms as biological catalysts to produce renewable energy and chemicals. To this end, autotrophic bacteria that are capable of fixing inorganic carbon in the form of CO2 and CO are of particular interest. Clostridium carboxidivorans is one such bacterium, an anaerobic acetogen capable of producing ethanol, butanol, hexanol, and their conjugate organic acids from CO or CO2 and H2. However, C. carboxidivorans possesses an expansive Restriction Modification System (RMS) rendering DNA transfer impossible. In this study, the RMS of C. carboxidivorans is bypassed to deliver CRISPR-Cas9 vectors targeting RMS-associated nuclease-encoding genes to create a fully genetically domesticated strain, C. carboxidivorans Δ7RM. Then, a metabolic engineering approach is adopted whereby the gene hytA of the domesticated strain is deleted to increase autotrophic growth and ethanol, butanol, and hexanol production. Finally, an alternative Retrotransposition Activated Marker is developed for the ClosTron mutagenesis system. This is characterised in several members of Clostridium, including C. carboxidivorans Δ7RM.